Pharmacokinetic and pharmacodynamic bioequivalence of biosimilar MYL‐1601D with US and European insulin aspart in healthy volunteers: A randomized, double‐blind, crossover, euglycaemic glucose clamp study. Issue 12 (25th August 2021) - Hövelmann, Ulrike; Raiter, Yaron; Chullikana, Anoop; Liu, Mark; Donnelly, Charles; Lawrence, Tracey; Sengupta, Nilanjan; CL, Gopu; Ranganna, Gopinath; Barve, Abhijit
Abstract: Aim: To evaluate the pharmacokinetic (PK) and pharmacodynamic (PD) bioequivalence (BE) of MYL‐1601D biosimilar with originator, NovoLog (Ref‐InsAsp‐US), and NovoRapid (Ref‐InsAsp‐EU). Materials and Methods: This was a double‐blind, randomized, crossover study that enrolled 71 healthy subjects to receive a single subcutaneous dose (0.2 U/kg) of each formulation under automated euglycaemic clamp conditions (ClampArt, level 81 mg/dL, duration 12 hours postdose). Primary PK endpoints were area under the plasma insulin aspart concentration‐time curve from 0 to 12 hours (AUC0‐12h ) and maximum plasma insulin aspart concentration (Cmax ). Primary PD endpoints were area under the glucose infusion rate (GIR) time curve from 0 to 12 hours (AUCGIR0‐12h ) and maximum GIR (GIRmax ). Insulin aspart in plasma was quantified using immunoaffinity purification followed by ultraperformance liquid chromatography and tandem mass spectrometric detection. The pairwise comparisons of geometric least square mean (LS‐mean) ratio for a 90% confidence interval (CI) of primary PK, and 90% CIs (MYL‐1601D vs. Ref‐InsAsp‐US) and 95% CIs (MYL‐1601D vs. Ref‐InsAsp‐EU) of primary PD variables, were to be within 80% to 125% to show BE. Results: MYL‐1601D showed PK BE to both Ref‐InsAsp‐US (AUC0‐12h geometric LS‐mean ratio 102.17, 90% CI [100.26; 104.11]; Cmax 106.13 [100.71; 111.85]) and Ref‐InsAsp‐EU (AUC0‐12h 101.84 [100.04; 103.67]; Cmax 105.74 [101.09; 110.60]). Likewise, MYL‐1601D showed PD BE to Ref‐InsAsp‐US (AUCGIR_0‐last 99.93; 90% CI [95.74; 104.30]; GIR_max 100.12 [94.46; 106.12]) and Ref‐InsAsp‐EU (AUCGIR_0‐last 96.42; 95% CI [91.17; 101.98]; GIR_max 95.10 [89.37; 101.19]). All three insulin aspart products were well tolerated. Conclusion: MYL‐1601D showed BE to Ref‐InsAsp‐US and Ref‐InsAsp‐EU with a comparable safety profile.